Community Screening for Pre-Diabetes and Diabetes Using HbA1c Levels in High Risk African Americans and Latinos - Davidson, Mayer B. (Ethn Dis, 2014)
OBJECTIVE: To evaluate community screening using HbA1c levels in high risk African Americans and Latinos in those not known to have diabetes. DESIGN: HbA1c levels were measured in 1542 African Americans and Latinos aged ≥40 years with one or more of the following risk factors: family history in first degree relatives, waist circumference ≥40 inches in males or ≥35 inches in females, and hypertension, either treatment for or a measured BP of ≥140/90 mm Hg. Oral glucose tolerance tests (OGTT) were offered to those meeting the HbA1c criterion for pre-diabetes. SETTING: Churches, community health fares, senior citizen sites. PARTICIPANTS: People without known diabetes. MAIN OUTCOME MEASURES: Proportion of people meeting the HbA1c criteria for pre-diabetes (5.8-6.4%) and diabetes (≥6.5%). RESULTS: 32% had one, 50% had two and 18% had three risk factors. By HbA1c criteria, 40% had pre-diabetes and 25% had diabetes. Increased waist circumference was the most common risk factor followed by a positive family history, and lastly, hypertension. Each individual risk factor was significantly (P<.001) and progressively more common as glycemia increased. Each additional risk factor increased the odds of pre-diabetes or diabetes by 2- to 4- fold. In individuals with pre-diabetes who underwent an OGTT, 59% were normal, 35% had pre-diabetes and only 6% had diabetes. CONCLUSIONS: Community screening of high risk African Americans and Latinos with HbA1c levels identifies a large proportion of people with pre-diabetes and diabetes. Those identified with pre-diabetes are unlikely to meet the OGTT criteria for diabetes.